Optimizing the Performance of Bhabinkamtibmas Through Visiting Activities to Prevent Criminal Fraud in the Jurisdiction of Sragen Police - Sandy, Widya Serenia (Advances in Police Science Research Journal, 2024)
Cases of criminal acts of fraud in the jurisdiction of the Sragen Police have experienced an increase in the last three years.. Preventive efforts are the most effective efforts needed to reduce cases of criminal acts of fraud. Therefore, it is necessary to carry out research that aims to find out how the performance and management system are implemented by Bhabinkamtibmas in visiting activities. A qualitative approach with descriptive analysis research was used as the method in this study. Data was collected using interview, observation, and documentation techniques. This study uses POAC management theory and competency theory accompanied by the principle of Bhabinkamtibmas, the concept of visits, and deception. Based on the results of research in the field, the performance of Bhabinkamtibmas in preventing criminal acts of fraud in the jurisdiction of the Sragen Police is known to be still not optimal yet supported by several internal and external factors that can affect the performance of the Bhabinkamtibmas. Several factors delay the implementation of extension activities through these visits, both internal factors and external factors, such as the dual role played by Bhabinkamtibmas outside of functions and duties on essence, the written material regarding the Crime of Fraud has not been arranged. Meanwhile, from external factors, it was found that there was a lack of public knowledge regarding Fraud Crimes. The result of the research suggests that in the 'planning' stage, active plans should be well-prepared, the division of tasks following predetermined rules, and Bhabinkamtibmas can be more intense in providing counseling regarding Fraud Crimes.